Composite negative electrode, preparation method thereof and all-solid-state battery
By adopting a double-layer negative electrode active material layer structure in the negative electrode of an all-solid state battery, the second negative electrode active material layer with a high-content metal powder can alleviate the expansion of the silicon material, and the problem of volume expansion and structural collapse of the silicon-based negative electrode material during charging and discharging is solved, and the circulation performance and capacity density of the battery are improved.
Patent Information
- Application Number
- CN202411736455.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-05-02
AI Technical Summary
The silicon-based negative electrode material is prone to lithiation during charging and discharging, forming LixSi alloys, resulting in volume expansion and structural collapse, which in turn leads to battery capacity attenuation and deterioration of cycle performance.
The structure of a double-layer negative electrode active material layer is adopted. The first negative electrode active material layer includes silicon powder and a first metal powder, the second negative electrode active material layer includes silicon powder and a second metal powder. The mass proportion of the second metal powder is higher than that of the first metal powder, and a lithium-metal alloy is formed to alleviate the expansion of the silicon material.
It effectively alleviates the expansion of silicon material, reduces the risk of negative electrode cracking, and improves the cycling performance and capacity density of the battery.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery production, and in particular to a composite negative electrode and a preparation method thereof, and an all-solid-state battery. Background Art
[0002] As people's requirements for battery energy density continue to increase, traditional lithium-ion batteries have been difficult to meet the increasing demand for specific capacity. Technical personnel in the field have gradually shifted their research and development focus from traditional lithium-ion batteries to solid-state lithium metal batteries with high specific capacity advantages. However, since traditional commercial positive electrode materials, such as lithium iron phosphate batteries (LFP) and NCM lithium batteries, have approached their capacity limits, how to increase the gram capacity of negative electrode materials has become one of the important research directions. Among them, silicon-based negative electrode materials, as a high-energy-density negative electrode material, have a theoretical gram capacity of up to 4200mAh / g.
[0003] However, silicon-based negative electrodes are prone to lithiation during the charge and discharge process to form LixSi alloys, resulting in a volume expansion of more than 280%. In severe cases, the structure may collapse and fall off the current collector, causing the battery capacity to decay rapidly and the battery cycle performance to deteriorate.
[0004] Therefore, the market is in urgent need of a technical solution to solve the above problems. Summary of the invention
[0005] In order to solve the above problems, the present invention discloses a negative electrode and a preparation method, and an all-solid-state battery. The technical solution of the present invention is implemented as follows:
[0006] A first aspect of the present invention provides a composite negative electrode, which is used in an all-solid-state battery, and includes a first negative electrode active material layer and a second negative electrode active material layer;
[0007] The first negative electrode active material layer includes silicon powder and first metal powder;
[0008] The second negative electrode active material layer includes silicon powder and second metal powder;
[0009] The first negative electrode active material layer is disposed on at least one side of the negative electrode current collector, and the second negative electrode active material layer is disposed on a side of the first negative electrode active material layer away from the negative electrode current collector;
[0010] A mass proportion w2 of the second metal powder in the second negative electrode active material layer is greater than or equal to a mass proportion w1 of the first metal powder in the first negative electrode active material layer.
[0011] Preferably, the first metal powder and the second metal powder are independently selected from at least one of indium powder, tin powder, magnesium powder, copper powder, aluminum powder and iron powder.
[0012] Preferably, the first metal powder is indium powder and / or the second metal powder is indium powder.
[0013] Preferably, the mass proportion w2 of the second metal powder in the second negative electrode active material layer is 50% to 80%;
[0014] Preferably, the silicon powder accounts for 20% to 50% by mass in the second negative electrode active material layer.
[0015] Preferably, the mass proportion w1 of the first metal powder in the first negative electrode active material layer is 5% to 30%;
[0016] Preferably, the silicon powder accounts for 70% to 95% by mass in the first negative electrode active material layer.
[0017] Preferably, the porosity of the first negative electrode active material layer is 4% to 8%;
[0018] The porosity of the second negative electrode active material layer is 8% to 15%.
[0019] Preferably, the first negative electrode active material layer further includes a first binder; and / or,
[0020] The second negative electrode active material layer further includes a second binder.
[0021] Preferably, the thickness of the second negative electrode active material layer is less than the thickness of the first negative electrode active material layer;
[0022] The thickness of the first negative electrode active material layer is 10 μm to 30 μm;
[0023] The second negative electrode active material layer has a thickness of 5 μm to 10 μm.
[0024] A second aspect of the present invention provides a method for preparing a composite negative electrode, the method comprising the following steps:
[0025] S1, mixing silicon powder, a first metal powder and a first binder in a solvent to prepare a first negative electrode slurry;
[0026] S2, coating the first negative electrode slurry on at least one side of the negative electrode current collector, and forming a first negative electrode active material layer after drying;
[0027] S3, mixing silicon powder, a second metal powder and a second binder in a solvent to prepare a second negative electrode slurry;
[0028] S4, coating the second negative electrode slurry on the first negative electrode active material layer to form a second negative electrode active material layer;
[0029] S5, after drying, a composite negative electrode is formed.
[0030] The third aspect of the present invention proposes an all-solid-state battery, which includes a positive electrode, a solid electrolyte membrane and a composite negative electrode proposed in the first aspect or a composite negative electrode prepared by the method proposed in the second aspect, and the composite negative electrode does not contain a solid electrolyte material and a conductive agent.
[0031] The advantages of the present invention are as follows:
[0032] The present invention sets a double-layer negative electrode active material layer structure in the negative electrode, and adds the first metal powder and the second metal powder into the first negative electrode active material layer and the second negative electrode active material layer respectively, which can effectively alleviate the lithium precipitation caused by the insufficient kinetics of pure silicon material and effectively improve the safety performance of the battery.
[0033] The second metal powder in the second negative electrode active material layer of the present invention has a high mass proportion and reacts with ions to form a lithium-metal alloy during charging. The lithium-metal alloy is softer than the lithium-silicon alloy, which is beneficial for inhibiting the expansion of the silicon material, thereby reducing the cracking of the negative electrode and improving the cycle performance of the battery.
[0034] The all-solid-state battery negative electrode in the present invention does not contain a solid electrolyte and a conductive agent, which further improves the capacity density of the battery. DETAILED DESCRIPTION
[0035] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the description and claims of the present invention and any variations thereof are intended to cover non-exclusive inclusions.
[0037] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0038] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.
[0039] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects before and after are in an "or" relationship.
[0040] Throughout the present invention, numerical values represent approximate measures or limits of ranges to cover minor deviations from given values as well as embodiments with about the values mentioned and embodiments with the exact values mentioned. Except for the working examples provided at the end of the detailed description, all numerical values of parameters (e.g., amounts or conditions) in this specification (including the appended claims) should be understood to be modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. "About" indicates that the stated numerical value allows some minor imprecision (close to the exact value of the value to some extent; approximately or reasonably close to the value; almost). If the imprecision provided by "about" is not otherwise understood in this ordinary sense in the art, "about" as used in the present invention at least indicates the variation that can be produced by the ordinary methods of measuring and using such parameters. For example, "about" may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some aspects, optionally less than or equal to 0.1%.
[0041] Additionally, disclosure of ranges includes disclosure of all values within the entire range and further divided ranges, including endpoints and sub-ranges given for such ranges.
[0042] When silicon negative electrode is used as the negative electrode of all-solid-state battery, it has received widespread attention due to its excellent capacity characteristics. However, it is still inevitable that silicon undergoes lithiation to form LixSi alloy during charging, resulting in a volume expansion of more than 280%. In severe cases, the structure will collapse and fall off the current collector, and the battery's cycle performance will deteriorate.
[0043] In order to solve the above problem, the present invention proposes a technical solution.
[0044] The first aspect of the present invention provides a composite negative electrode, the composite negative electrode comprising a negative electrode current collector, a first negative electrode active material layer and a second negative electrode active material layer;
[0045] The first negative electrode active material layer includes silicon powder and first metal powder;
[0046] The second negative electrode active material layer includes silicon powder and second metal powder;
[0047] The first negative electrode active material layer is disposed on at least one side of the negative electrode current collector, and the second negative electrode active material layer is disposed on a side of the first negative electrode active material layer away from the negative electrode current collector;
[0048] The mass proportion w2 of the second metal powder in the second negative electrode active material layer is greater than or equal to the mass proportion w1 of the first metal powder in the first negative electrode active material layer.
[0049] The active material layer in the present invention is set to a double-layer structure, and metal powders are added to the first negative electrode active material layer and the second negative electrode active material layer respectively, which can effectively alleviate the lithium precipitation caused by the insufficient kinetics of pure silicon materials and effectively improve the safety performance of the battery. The metal powder can also reduce the capacity loss caused by the reduction of silicon content in the negative electrode. In addition, the ionic conductivity of the metal powder is greater than that of the silicon powder, which is beneficial to the rapid transmission of lithium ions in the negative electrode and the energy density of the battery.
[0050] Among them, the metal powder mass proportion in the second negative electrode active material layer is high, and it reacts with ions to form lithium-metal alloy during charging. The lithium-metal alloy is softer than the lithium-silicon alloy and can effectively inhibit the expansion of the silicon material. It effectively alleviates the rapid attenuation of battery capacity and degradation of battery cycle performance caused by the expansion of silicon material and falling off the current collector.
[0051] In some embodiments, the first metal powder includes at least one of indium powder, tin powder, magnesium powder, copper powder, aluminum powder, and iron powder; and / or,
[0052] The second metal powder includes at least one of indium powder, tin powder, magnesium powder, copper powder, aluminum powder, and iron powder.
[0053] The term "at least one" as used in the present invention refers to any one of the materials listed above, or more than one material can be selected and mixed. The present invention can be freely implemented within the scope of understanding of those skilled in the art. The present invention does not impose any limitation on this.
[0054] In some more preferred embodiments, the first metal powder is indium powder and / or the second metal powder is indium powder.
[0055] In some embodiments, the mass proportion w2 of the second metal powder in the second negative electrode active material layer is 50% to 80%;
[0056] In some preferred embodiments, the mass percentage of silicon powder in the second negative electrode active material layer is 20% to 50%.
[0057] In the present invention, the second metal powder in the second negative electrode active material layer accounts for a relatively high proportion by mass. The second metal powder will undergo lithiation with lithium ions, and the formed Li-metal alloy has better flexibility than silicon material, which is beneficial for buffering the volume expansion caused by the silicon lithiation process in the first negative electrode active material layer, and is beneficial for improving the cycle performance of the battery.
[0058] In specific applications, the mass proportion of the second metal powder in the second negative electrode active material layer can be selected to be 50%, 60%, 70%, 80%, etc.; the mass proportion of the silicon powder in the second negative electrode active material layer can be selected to be 20%, 30%, 40%, 50%, etc. The above values are only examples and are not limiting.
[0059] In some embodiments, the mass proportion w1 of the first metal powder in the first negative electrode active material layer is 5% to 30%;
[0060] In some preferred embodiments, the mass percentage of silicon powder in the first negative electrode active material layer is 70% to 95%.
[0061] The silicon powder content in the first negative electrode active material layer is relatively high, which can ensure the capacity of the battery. Adding metal powder therein can improve the lithium precipitation problem caused by pure silicon material and further enhance the safety performance of the battery.
[0062] In specific applications, the mass proportion of the first metal powder in the first negative electrode active material layer can be 5%, 10%, 15%, 20%, 25%, 30%, etc.; the mass proportion of the silicon powder in the first negative electrode active material layer can be 70%, 75%, 80%, 85%, 90%, 95%, etc. The above values are only examples and are not limiting.
[0063] In some preferred embodiments, the particle size ratio of silicon powder to first metal powder in the first negative electrode active material layer is 10:1 to 100:1, and the particle size ratio of silicon powder to second metal powder in the second negative electrode active material layer is 10:1 to 100:1.
[0064] If the particle size ratio of silicon powder to metal powder is too small, gaps will accumulate between the powder particles. The ionic conductivity and electronic conductivity in the gaps are poor, and lithium deposition is likely to occur, leading to battery failure. Therefore, limiting the particle size ratio of silicon powder to the first metal powder and the second metal powder to the above range can effectively avoid lithium deposition.
[0065] In specific applications, the particle size ratio of silicon powder to the first metal powder and the second metal powder can be selected from any value in the above range, in addition to the end points of the above range 10:1 and 100:1, for example, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, etc. The above values are only examples and are not limiting.
[0066] In some embodiments, the porosity of the first negative electrode active material layer is 4% to 8%;
[0067] In some embodiments, the porosity of the second negative active material layer is 8% to 15%.
[0068] In some embodiments, the first negative electrode active material layer further includes a first binder and / or the second negative electrode active material layer further includes a second binder.
[0069] In some preferred embodiments, the mass proportion of the first binder in the first negative electrode active material layer is 0.1% to 2% and / or the mass proportion of the second binder in the second negative electrode active material layer is 0.1% to 2%.
[0070] In specific applications, the first binder and the second binder are independently selected from one or more of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), polyvinyl alcohol, polyacrylic acid, polyethylene glycol, polyethylene oxide, poly(p-phenylene ether), poly(methyl methacrylate), polyacrylonitrile, or polyvinyl chloride (PVC), all of which are common binders in the art and are only examples and not limitations.
[0071] In some more preferred embodiments, the mass proportion of the first binder in the first negative electrode active material layer is greater than the mass proportion of the second binder in the second negative electrode.
[0072] The advantage of such a configuration is that it helps prevent the negative electrode from falling off the negative electrode current collector.
[0073] In some embodiments, the thickness of the second negative electrode active material layer is less than the thickness of the first negative electrode active material layer;
[0074] The thickness of the first negative electrode active material layer is 10 μm to 30 μm;
[0075] The thickness of the second negative electrode active material layer is 5 μm to 10 μm.
[0076] The advantage of this arrangement is that it facilitates the rapid passage of lithium ions through the second active material layer, which is beneficial to the utilization of the battery capacity.
[0077] In specific applications, the thickness of the first negative electrode active material layer can be 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, etc.; the thickness of the second negative electrode active material layer can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc. The above values are only examples, and the present invention does not impose any limitation on this as long as the thickness of the first negative electrode active material layer is greater than the thickness of the second negative electrode active material layer.
[0078] A second aspect of the present invention provides a method for preparing a composite negative electrode, the method comprising the following steps:
[0079] S1, mixing silicon powder, a first metal powder and a first binder in a solvent to prepare a first negative electrode slurry;
[0080] S2, coating the first negative electrode slurry on at least one side of the negative electrode current collector, and forming a first negative electrode active material layer after drying;
[0081] S3, mixing silicon powder, a second metal powder and a second binder in a solvent to prepare a second negative electrode slurry;
[0082] S4, coating the second negative electrode slurry on the first negative electrode active material layer to form a second negative electrode active material layer;
[0083] S5, after drying, a composite negative electrode is formed.
[0084] In some preferred embodiments, S1 may further include the following steps:
[0085] S1.1, mixing silicon powder with a first metal powder to form a first mixture;
[0086] S1.2, mixing the first mixed material with a binder and a solvent to form a first negative electrode slurry.
[0087] In some more preferred embodiments, S3 may further include the following steps:
[0088] S3.1, mixing silicon powder with a second metal powder to form a second mixture;
[0089] S3.2, mixing the second mixed material with a binder and a solvent to form a second negative electrode slurry.
[0090] The third aspect of the present invention proposes an all-solid-state battery, which includes a positive electrode, a solid electrolyte membrane and a composite negative electrode as proposed in the first aspect or a composite negative electrode prepared by the method proposed in the second aspect, and the composite negative electrode does not contain a solid electrolyte material and a conductive agent.
[0091] Since the first metal powder and the second metal powder are conductive themselves and can also serve as carriers of battery capacity, the composite negative electrode proposed in the present invention does not require solid electrolyte materials and conductive agents. This arrangement is beneficial to improving the capacity density of the battery.
[0092] The invention comprises a positive electrode, a solid electrolyte membrane and a negative electrode, wherein the negative electrode is the negative electrode as described in the first aspect or the negative electrode prepared by the method as described in the second aspect, and the negative electrode does not contain a solid electrolyte.
[0093] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer includes a positive electrode active material, a conductive agent, and a binder.
[0094] In specific applications, the positive electrode active material can be selected to include any one or a combination of at least two of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, lithium iron phosphate, lithium titanate or lithium-rich manganese elastic-based materials. The above are all common positive electrode active materials in the art, which are only examples and not limitations.
[0095] In specific applications, the conductive agent may include any conductive material as long as it does not cause chemical changes. Conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof. The above are all common conductive agents in the art, which are only examples and not limitations.
[0096] In specific applications, the binder may include at least one of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), polyvinyl alcohol, polyacrylic acid, polyethylene glycol, polyethylene oxide, poly(p-phenylene oxide), poly(methyl methacrylate), polyacrylonitrile, or polyvinyl chloride (PVC). The above are all common binders in the art, which are only examples and not limitations.
[0097] In some embodiments, the solid electrolyte membrane includes any one or a combination of at least two of a sulfide solid electrolyte, a halide solid electrolyte, and an oxide solid electrolyte. The above are all common solid electrolytes in the art and are only examples and not limitations.
[0098] In some preferred embodiments, the solid electrolyte membrane material may be a sulfide solid electrolyte.
[0099] In specific applications, the sulfide solid electrolyte can be selected from: Li2S-P2S5, Li2S-P2S5-MS x (where M is Si, Ge and Sn and 0≤x≤2), Li 3.4Si 0.4 P 0.6 S4, Li 10 GeP2S 11.7 O 0.3 , Li 9.6 P3S 12 , Li7P3S 11 , Li9P3S9O3, Li 10.35 Si 1.35 P 1.65 S 12 , Li 9.81 Sn 0.81 P 2.19 S 12 , Li 10 (Si 0.5 Ge 0.5 )P2S 12 , Li(Ge 0.5 Sn 0.5 )P2S 12 , Li(Si 0.5 Sn 0.5 )PsS 12 , Li 10 GeP2S 12 (LGPS), Li6PS5X (where X is Cl, Br or I), Li7P2S8I, Li 10.35 Ge 1.35 P 1.65 S 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li 10 SnP2S 12 , Li 10 SiP2S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 C l0.3 , (1-x) P2S 5-x at least one of Li2S (where 0.5 ≤ x ≤ 0.7).
[0100] In a specific application, the halide solid electrolyte can be selected from: Li2CdC l4 , Li2MgC l4 , Li2Cd I4 , Li2ZnI4, Li3OCl, LiI, Li5ZnI4, Li3OCl 1-x Br x (where 0 < x < 1).
[0101] In specific applications, the oxide solid electrolyte can be selected from: perovskite type, garnet type, LISICON type, NASICON type, wherein the perovskite type solid electrolyte material is preferably LLTO (lithium lanthanum titanate / lithium lanthanum titanate, Li 0.33 La 0.56 TiO3), the garnet-type solid electrolyte material is preferably LLZO (lithium zirconium oxide / lithium lanthanum zirconate, Li7La3Zr2O 12 ), NASICON (sodium super ion conductor) type solid electrolyte material is preferably lithium aluminum titanium phosphate LATPLi 1.3 Al 0.3 Ti 1.7 (PO4)3) at least one.
[0102] The embodiments of the present invention will be described in detail below through examples and comparative examples. All examples and comparative examples are all solid-state battery sample groups prepared by the same process, and the number of samples in each group is 20.
[0103] It should be noted that the embodiments of the present invention are not limited to these examples.
[0104] Example 1
[0105] 1. Preparation of positive electrode:
[0106] The positive electrode active material LCO, the binder PVDF, and the conductive agent super-P are mixed evenly in a mass ratio of 95:3:2, and placed in a high shear force equipment mixer for fiberization to form a mixture, which is then rolled to form the first positive electrode active material layer; the rolling temperature is 60°C, and the rolling time is 5 minutes; the positive electrode current collector and the first positive electrode active material layer are stacked, hot-pressed, and cooled to form a composite positive electrode. The hot-pressing temperature is 150°C, the hot-pressing time is 10 minutes, and the hot-pressing pressure is 120Mpa.
[0107] 2. Preparation of negative electrode:
[0108] S1, preparing a first negative electrode slurry;
[0109] S1.1, mixing silicon powder and indium powder to form a first mixture;
[0110] S1.2, mixing the first mixed material, the binder PVDF, and the solvent NMP to form a first negative electrode slurry;
[0111] The mass ratio of indium powder, silicon powder and binder PVDF is 20:78.5:1.5; the particle size ratio of silicon powder to indium powder is 20:1;
[0112] S2, coating the first negative electrode slurry on at least one side of the negative electrode current collector, and forming a first negative electrode active material layer after drying;
[0113] S3, preparing a second negative electrode slurry;
[0114] S3.1, mixing silicon powder and indium powder to form a second mixture;
[0115] S3.2, mixing the second mixed material, the binder PVDF, and the solvent NMP to form a second negative electrode slurry; the mass ratio of indium powder, silicon powder, and binder PVDF is 70:28.5:1.5; the particle size ratio of silicon powder to indium powder is 20:1;
[0116] S4, coating the second negative electrode slurry on the first negative electrode active material layer to form a second negative electrode active material layer;
[0117] S5, after drying, a composite negative electrode is formed.
[0118] The thickness of the first negative electrode active material layer is 20 μm, and the thickness of the second negative electrode active material layer is 8 μm.
[0119] 3. Preparation of solid electrolyte membrane
[0120] The sulfide electrolyte Li6PS5Cl and the binder (PVDF) were mixed in a mass ratio of 99:1 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.
[0121] 4. Preparation of all-solid-state batteries
[0122] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.
[0123] Example 2
[0124] 1. Preparation of positive electrode:
[0125] The positive electrode active material LCO, the binder PVDF, and the conductive agent super-P are mixed evenly in a mass ratio of 95:3:2, and placed in a high shear force equipment mixer for fiberization to form a mixture, which is then rolled to form the first positive electrode active material layer; the rolling temperature is 60°C, and the rolling time is 5 minutes; the positive electrode current collector and the first positive electrode active material layer are stacked, hot-pressed, and cooled to form a composite positive electrode. The hot-pressing temperature is 150°C, the hot-pressing time is 10 minutes, and the hot-pressing pressure is 120Mpa.
[0126] 2. Preparation of negative electrode:
[0127] S1, preparing a first negative electrode slurry;
[0128] S1.1, mixing silicon powder and indium powder to form a first mixture;
[0129] S1.2, mixing the first mixed material, the binder PVDF, and the solvent NMP to form a first negative electrode slurry;
[0130] The mass ratio of indium powder, silicon powder and binder PVDF is 5:93.5:1.5; the particle size ratio of silicon powder to indium powder is 20:1;
[0131] S2, coating the first negative electrode slurry on at least one side of the negative electrode current collector, and forming a first negative electrode active material layer after drying;
[0132] S3, preparing a second negative electrode slurry;
[0133] S3.1, mixing silicon powder and indium powder to form a second mixture;
[0134] S3.2, mixing the second mixed material, the binder PVDF, and the solvent NMP to form a second negative electrode slurry; the mass ratio of indium powder, silicon powder, and binder PVDF is 70:28.5:1.5; the particle size ratio of silicon powder to indium powder is 20:1;
[0135] S4, coating the second negative electrode slurry on the first negative electrode active material layer to form a second negative electrode active material layer;
[0136] S5, after drying, a composite negative electrode is formed.
[0137] The thickness of the first negative electrode active material layer is 20 μm, and the thickness of the second negative electrode active material layer is 8 μm.
[0138] 3. Preparation of solid electrolyte membrane
[0139] The sulfide electrolyte Li6PS5Cl and the binder (PVDF) were mixed in a mass ratio of 99:1 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.
[0140] 4. Preparation of all-solid-state batteries
[0141] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.
[0142] Example 3
[0143] 1. Preparation of positive electrode:
[0144] The positive electrode active material LCO, the binder PVDF, and the conductive agent super-P are mixed evenly in a mass ratio of 95:3:2, and placed in a high shear force equipment mixer for fiberization to form a mixture, which is then rolled to form the first positive electrode active material layer; the rolling temperature is 60°C, and the rolling time is 5 minutes; the positive electrode current collector and the first positive electrode active material layer are stacked, hot-pressed, and cooled to form a composite positive electrode. The hot-pressing temperature is 150°C, the hot-pressing time is 10 minutes, and the hot-pressing pressure is 120Mpa.
[0145] 2. Preparation of negative electrode:
[0146] S1, preparing a first negative electrode slurry;
[0147] S1.1, mixing silicon powder and indium powder to form a first mixture;
[0148] S1.2, mixing the first mixed material, the binder PVDF, and the solvent NMP to form a first negative electrode slurry;
[0149] The mass ratio of indium powder, silicon powder and binder PVDF is 30:68.5:1.5; the particle size ratio of silicon powder to indium powder is 20:1;
[0150] S2, coating the first negative electrode slurry on at least one side of the negative electrode current collector, and forming a first negative electrode active material layer after drying;
[0151] S3, preparing a second negative electrode slurry;
[0152] S3.1, mixing silicon powder and indium powder to form a second mixture;
[0153] S3.2, mixing the second mixed material, the binder PVDF, and the solvent NMP to form a second negative electrode slurry; the mass ratio of indium powder, silicon powder, and binder PVDF is 70:28.5:1.5; the particle size ratio of silicon powder to indium powder is 20:1;
[0154] S4, coating the second negative electrode slurry on the first negative electrode active material layer to form a second negative electrode active material layer;
[0155] S5, after drying, a composite negative electrode is formed.
[0156] The thickness of the first negative electrode active material layer is 20 μm, and the thickness of the second negative electrode active material layer is 8 μm.
[0157] 3. Preparation of solid electrolyte membrane
[0158] The sulfide electrolyte Li6PS5Cl and the binder (PVDF) were mixed in a mass ratio of 99:1 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.
[0159] 4. Preparation of all-solid-state batteries
[0160] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.
[0161] Example 4
[0162] 1. Preparation of positive electrode:
[0163] The positive electrode active material LCO, the binder PVDF, and the conductive agent super-P are mixed evenly in a mass ratio of 95:3:2, and placed in a high shear force equipment mixer for fiberization to form a mixture, which is then rolled to form the first positive electrode active material layer; the rolling temperature is 60°C, and the rolling time is 5 minutes; the positive electrode current collector and the first positive electrode active material layer are stacked, hot-pressed, and cooled to form a composite positive electrode. The hot-pressing temperature is 150°C, the hot-pressing time is 10 minutes, and the hot-pressing pressure is 120Mpa.
[0164] 2. Preparation of negative electrode:
[0165] S1, preparing a first negative electrode slurry;
[0166] S1.1, mixing silicon powder and indium powder to form a first mixture;
[0167] S1.2, mixing the first mixed material, the binder PVDF, and the solvent NMP to form a first negative electrode slurry;
[0168] The mass ratio of indium powder, silicon powder and binder PVDF is 20:78.5:1.5; the particle size ratio of silicon powder to indium powder is 20:1;
[0169] S2, coating the first negative electrode slurry on at least one side of the negative electrode current collector, and forming a first negative electrode active material layer after drying;
[0170] S3, preparing a second negative electrode slurry;
[0171] S3.1, mixing silicon powder and indium powder to form a second mixture;
[0172] S3.2, mixing the second mixed material, the binder PVDF, and the solvent NMP to form a second negative electrode slurry; the mass ratio of indium powder, silicon powder, and binder PVDF is 50:48.5:1.5; the particle size ratio of silicon powder to indium powder is 20:1;
[0173] S4, coating the second negative electrode slurry on the first negative electrode active material layer to form a second negative electrode active material layer;
[0174] S5, after drying, a composite negative electrode is formed.
[0175] The thickness of the first negative electrode active material layer is 20 μm, and the thickness of the second negative electrode active material layer is 8 μm.
[0176] 3. Preparation of solid electrolyte membrane
[0177] The sulfide electrolyte Li6PS5Cl and the binder (PVDF) were mixed in a mass ratio of 99:1 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.
[0178] 4. Preparation of all-solid-state batteries
[0179] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.
[0180] Example 5
[0181] 1. Preparation of positive electrode:
[0182] The positive electrode active material LCO, the binder PVDF, and the conductive agent super-P are mixed evenly in a mass ratio of 95:3:2, and placed in a high shear force equipment mixer for fiberization to form a mixture, which is then rolled to form the first positive electrode active material layer; the rolling temperature is 60°C, and the rolling time is 5 minutes; the positive electrode current collector and the first positive electrode active material layer are stacked, hot-pressed, and cooled to form a composite positive electrode. The hot-pressing temperature is 150°C, the hot-pressing time is 10 minutes, and the hot-pressing pressure is 120Mpa.
[0183] 2. Preparation of negative electrode:
[0184] S1, preparing a first negative electrode slurry;
[0185] S1.1, mixing silicon powder and indium powder to form a first mixture;
[0186] S1.2, mixing the first mixed material, the binder PVDF, and the solvent NMP to form a first negative electrode slurry;
[0187] The mass ratio of indium powder, silicon powder and binder PVDF is 20:78.5:1.5; the particle size ratio of silicon powder to indium powder is 20:1;
[0188] S2, coating the first negative electrode slurry on at least one side of the negative electrode current collector, and forming a first negative electrode active material layer after drying;
[0189] S3, preparing a second negative electrode slurry;
[0190] S3.1, mixing silicon powder and indium powder to form a second mixture;
[0191] S3.2, mixing the second mixed material, the binder PVDF, and the solvent NMP to form a second negative electrode slurry; the mass ratio of indium powder, silicon powder, and binder PVDF is 80:18.5:1.5; the particle size ratio of silicon powder to indium powder is 20:1;
[0192] S4, coating the second negative electrode slurry on the first negative electrode active material layer to form a second negative electrode active material layer;
[0193] S5, after drying, a composite negative electrode is formed.
[0194] The thickness of the first negative electrode active material layer is 20 μm, and the thickness of the second negative electrode active material layer is 8 μm.
[0195] 3. Preparation of solid electrolyte membrane
[0196] The sulfide electrolyte Li6PS5Cl and the binder (PVDF) were mixed in a mass ratio of 99:1 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.
[0197] 4. Preparation of all-solid-state batteries
[0198] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.
[0199] Example 6
[0200] 1. Preparation of positive electrode:
[0201] The positive electrode active material LCO, the binder PVDF, and the conductive agent super-P are mixed evenly in a mass ratio of 95:3:2, and placed in a high shear force equipment mixer for fiberization to form a mixture, which is then rolled to form the first positive electrode active material layer; the rolling temperature is 60°C, and the rolling time is 5 minutes; the positive electrode current collector and the first positive electrode active material layer are stacked, hot-pressed, and cooled to form a composite positive electrode. The hot-pressing temperature is 150°C, the hot-pressing time is 10 minutes, and the hot-pressing pressure is 120Mpa.
[0202] 2. Preparation of negative electrode:
[0203] S1, preparing a first negative electrode slurry;
[0204] S1.1, mixing silicon powder and indium powder to form a first mixture;
[0205] S1.2, mixing the first mixed material, the binder PVDF, and the solvent NMP to form a first negative electrode slurry;
[0206] The mass ratio of indium powder, silicon powder and binder PVDF is 20:78.5:1.5; the particle size ratio of silicon powder to indium powder is 10:1;
[0207] S2, coating the first negative electrode slurry on at least one side of the negative electrode current collector, and forming a first negative electrode active material layer after drying;
[0208] S3, preparing a second negative electrode slurry;
[0209] S3.1, mixing silicon powder and indium powder to form a second mixture;
[0210] S3.2, mixing the second mixed material, the binder PVDF, and the solvent NMP to form a second negative electrode slurry; the mass ratio of indium powder, silicon powder, and binder PVDF is 70:28.5:1.5; the particle size ratio of silicon powder to indium powder is 50:1;
[0211] S4, coating the second negative electrode slurry on the first negative electrode active material layer to form a second negative electrode active material layer;
[0212] S5, after drying, a composite negative electrode is formed.
[0213] The thickness of the first negative electrode active material layer is 20 μm, and the thickness of the second negative electrode active material layer is 8 μm.
[0214] 3. Preparation of solid electrolyte membrane
[0215] The sulfide electrolyte Li6PS5Cl and the binder (PVDF) were mixed in a mass ratio of 99:1 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.
[0216] 4. Preparation of all-solid-state batteries
[0217] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.
[0218] Example 7
[0219] 1. Preparation of positive electrode:
[0220] The positive electrode active material LCO, the binder PVDF, and the conductive agent super-P are mixed evenly in a mass ratio of 95:3:2, and placed in a high shear force equipment mixer for fiberization to form a mixture, which is then rolled to form the first positive electrode active material layer; the rolling temperature is 60°C, and the rolling time is 5 minutes; the positive electrode current collector and the first positive electrode active material layer are stacked, hot-pressed, and cooled to form a composite positive electrode. The hot-pressing temperature is 150°C, the hot-pressing time is 10 minutes, and the hot-pressing pressure is 120Mpa.
[0221] 2. Preparation of negative electrode:
[0222] S1, preparing a first negative electrode slurry;
[0223] S1.1, mixing silicon powder and tin powder to form a first mixture;
[0224] S1.2, mixing the first mixed material, the binder PVDF, and the solvent NMP to form a first negative electrode slurry;
[0225] The mass ratio of tin powder, silicon powder and binder PVDF is 20:78.5:1.5; the particle size ratio of silicon powder to tin powder is 20:1;
[0226] S2, coating the first negative electrode slurry on at least one side of the negative electrode current collector, and forming a first negative electrode active material layer after drying;
[0227] S3, preparing a second negative electrode slurry;
[0228] S3.1, mixing silicon powder and indium powder to form a second mixture;
[0229] S3.2, mixing the second mixed material, the binder PVDF, and the solvent NMP to form a second negative electrode slurry; the mass ratio of indium powder, silicon powder, and binder PVDF is 70:28.5:1.5; the particle size ratio of silicon powder to indium powder is 20:1;
[0230] S4, coating the second negative electrode slurry on the first negative electrode active material layer to form a second negative electrode active material layer;
[0231] S5, after drying, a composite negative electrode is formed.
[0232] The thickness of the first negative electrode active material layer is 20 μm, and the thickness of the second negative electrode active material layer is 8 μm.
[0233] 3. Preparation of solid electrolyte membrane
[0234] The sulfide electrolyte Li6PS5Cl and the binder (PVDF) were mixed in a mass ratio of 99:1 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.
[0235] 4. Preparation of all-solid-state batteries
[0236] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.
[0237] Example 8
[0238] 1. Preparation of positive electrode:
[0239] The positive electrode active material LCO, the binder PVDF, and the conductive agent super-P are mixed evenly in a mass ratio of 95:3:2, and placed in a high shear force equipment mixer for fiberization to form a mixture, which is then rolled to form the first positive electrode active material layer; the rolling temperature is 60°C, and the rolling time is 5 minutes; the positive electrode current collector and the first positive electrode active material layer are stacked, hot-pressed, and cooled to form a composite positive electrode. The hot-pressing temperature is 150°C, the hot-pressing time is 10 minutes, and the hot-pressing pressure is 120Mpa.
[0240] 2. Preparation of negative electrode:
[0241] S1, preparing a first negative electrode slurry;
[0242] S1.1, mixing silicon powder and aluminum powder to form a first mixture;
[0243] S1.2, mixing the first mixed material, the binder PVDF, and the solvent NMP to form a first negative electrode slurry;
[0244] The mass ratio of aluminum powder, silicon powder and binder PVDF is 20:78.5:1.5; the particle size ratio of silicon powder to aluminum powder is 20:1;
[0245] S2, coating the first negative electrode slurry on at least one side of the negative electrode current collector, and forming a first negative electrode active material layer after drying;
[0246] S3, preparing a second negative electrode slurry;
[0247] S3.1, mixing silicon powder and tin powder to form a second mixture;
[0248] S3.2, mixing the second mixed material, the binder PVDF, and the solvent NMP to form a second negative electrode slurry; the mass ratio of tin powder, silicon powder, and the binder PVDF is 70:28.5:1.5; the particle size ratio of silicon powder to tin powder is 20:1;
[0249] S4, coating the second negative electrode slurry on the first negative electrode active material layer to form a second negative electrode active material layer;
[0250] S5, after drying, a composite negative electrode is formed.
[0251] The thickness of the first negative electrode active material layer is 20 μm, and the thickness of the second negative electrode active material layer is 8 μm.
[0252] 3. Preparation of solid electrolyte membrane
[0253] The sulfide electrolyte Li6PS5Cl and the binder (PVDF) were mixed in a mass ratio of 99:1 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.
[0254] 4. Preparation of all-solid-state batteries
[0255] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.
[0256] Example 9
[0257] 1. Preparation of positive electrode:
[0258] The positive electrode active material LCO, the binder PVDF, and the conductive agent super-P are mixed evenly in a mass ratio of 95:3:2, and placed in a high shear force equipment mixer for fiberization to form a mixture, which is then rolled to form the first positive electrode active material layer; the rolling temperature is 60°C, and the rolling time is 5 minutes; the positive electrode current collector and the first positive electrode active material layer are stacked, hot-pressed, and cooled to form a composite positive electrode. The hot-pressing temperature is 150°C, the hot-pressing time is 10 minutes, and the hot-pressing pressure is 120Mpa.
[0259] 2. Preparation of negative electrode:
[0260] S1, preparing a first negative electrode slurry;
[0261] S1.1, mixing silicon powder and indium powder to form a first mixture;
[0262] S1.2, mixing the first mixed material, the binder PVDF, and the solvent NMP to form a first negative electrode slurry;
[0263] The mass ratio of indium powder, silicon powder and binder PVDF is 20:78.5:1.5; the particle size ratio of silicon powder to indium powder is 20:1;
[0264] S2, coating the first negative electrode slurry on at least one side of the negative electrode current collector, and forming a first negative electrode active material layer after drying;
[0265] S3, preparing a second negative electrode slurry;
[0266] S3.1, mixing silicon powder and indium powder to form a second mixture;
[0267] S3.2, mixing the second mixed material, the binder PVDF, and the solvent NMP to form a second negative electrode slurry; the mass ratio of indium powder, silicon powder, and binder PVDF is 70:28.5:1.5; the particle size ratio of silicon powder to indium powder is 20:1;
[0268] S4, coating the second negative electrode slurry on the first negative electrode active material layer to form a second negative electrode active material layer;
[0269] S5, after drying, a composite negative electrode is formed.
[0270] The thickness of the first negative electrode active material layer is 10 μm, and the thickness of the second negative electrode active material layer is 5 μm.
[0271] 3. Preparation of solid electrolyte membrane
[0272] The sulfide electrolyte Li6PS5Cl and the binder (PVDF) were mixed in a mass ratio of 99:1 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.
[0273] 4. Preparation of all-solid-state batteries
[0274] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.
[0275] Example 10
[0276] 1. Preparation of positive electrode:
[0277] The positive electrode active material LCO, the binder PVDF, and the conductive agent super-P are mixed evenly in a mass ratio of 95:3:2, and placed in a high shear force equipment mixer for fiberization to form a mixture, which is then rolled to form the first positive electrode active material layer; the rolling temperature is 60°C, and the rolling time is 5 minutes; the positive electrode current collector and the first positive electrode active material layer are stacked, hot-pressed, and cooled to form a composite positive electrode. The hot-pressing temperature is 150°C, the hot-pressing time is 10 minutes, and the hot-pressing pressure is 120Mpa.
[0278] 2. Preparation of negative electrode:
[0279] S1, preparing a first negative electrode slurry;
[0280] S1.1, mixing silicon powder and indium powder to form a first mixture;
[0281] S1.2, mixing the first mixed material, the binder PVDF, and the solvent NMP to form a first negative electrode slurry;
[0282] The mass ratio of indium powder, silicon powder and binder PVDF is 20:78.5:1.5; the particle size ratio of silicon powder to indium powder is 20:1;
[0283] S2, coating the first negative electrode slurry on at least one side of the negative electrode current collector, and forming a first negative electrode active material layer after drying;
[0284] S3, preparing a second negative electrode slurry;
[0285] S3.1, mixing silicon powder and indium powder to form a second mixture;
[0286] S3.2, mixing the second mixed material, the binder PVDF, and the solvent NMP to form a second negative electrode slurry; the mass ratio of indium powder, silicon powder, and binder PVDF is 70:28.5:1.5; the particle size ratio of silicon powder to indium powder is 20:1;
[0287] S4, coating the second negative electrode slurry on the first negative electrode active material layer to form a second negative electrode active material layer;
[0288] S5, after drying, a composite negative electrode is formed.
[0289] The thickness of the first negative electrode active material layer is 30 μm, and the thickness of the second negative electrode active material layer is 10 μm.
[0290] 3. Preparation of solid electrolyte membrane
[0291] The sulfide electrolyte Li6PS5Cl and the binder (PVDF) were mixed in a mass ratio of 99:1 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.
[0292] 4. Preparation of all-solid-state batteries
[0293] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.
[0294] Embodiment 11
[0295] 1. Preparation of positive electrode:
[0296] The positive electrode active material LCO, the binder PVDF, and the conductive agent super-P are mixed evenly in a mass ratio of 95:3:2, and placed in a high shear force equipment mixer for fiberization to form a mixture, which is then rolled to form the first positive electrode active material layer; the rolling temperature is 60°C, and the rolling time is 5 minutes; the positive electrode current collector and the first positive electrode active material layer are stacked, hot-pressed, and cooled to form a composite positive electrode. The hot-pressing temperature is 150°C, the hot-pressing time is 10 minutes, and the hot-pressing pressure is 120Mpa.
[0297] 2. Preparation of negative electrode:
[0298] S1, preparing a first negative electrode slurry;
[0299] S1.1, mixing silicon powder and indium powder to form a first mixture;
[0300] S1.2, mixing the first mixed material, the binder PVDF, and the solvent NMP to form a first negative electrode slurry;
[0301] The mass ratio of indium powder, silicon powder and binder PVDF is 20:78.5:1.5; the particle size ratio of silicon powder to indium powder is 20:1;
[0302] S2, coating the first negative electrode slurry on at least one side of the negative electrode current collector, and forming a first negative electrode active material layer after drying;
[0303] S3, preparing a second negative electrode slurry;
[0304] S3.1, mixing silicon powder and indium powder to form a second mixture;
[0305] S3.2, mixing the second mixed material, the binder PVDF, and the solvent NMP to form a second negative electrode slurry; the mass ratio of indium powder, silicon powder, and binder PVDF is 70:28.5:1.5; the particle size ratio of silicon powder to indium powder is 20:1;
[0306] S4, coating the second negative electrode slurry on the first negative electrode active material layer to form a second negative electrode active material layer;
[0307] S5, after drying, a composite negative electrode is formed.
[0308] The thickness of the first negative electrode active material layer is 10 μm, and the thickness of the second negative electrode active material layer is 10 μm.
[0309] 3. Preparation of solid electrolyte membrane
[0310] The sulfide electrolyte Li6PS5Cl and the binder (PVDF) were mixed in a mass ratio of 99:1 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.
[0311] 4. Preparation of all-solid-state batteries
[0312] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.
[0313] Comparative Example 1
[0314] 1. Preparation of positive electrode:
[0315] The positive electrode active material LCO, the binder PVDF, and the conductive agent super-P are mixed evenly in a mass ratio of 95:3:2, and placed in a high shear force equipment mixer for fiberization to form a mixture, which is then rolled to form the first positive electrode active material layer; the rolling temperature is 60°C, and the rolling time is 5 minutes; the positive electrode current collector and the first positive electrode active material layer are stacked, hot-pressed, and cooled to form a composite positive electrode. The hot-pressing temperature is 150°C, the hot-pressing time is 10 minutes, and the hot-pressing pressure is 120Mpa.
[0316] 2. Preparation of negative electrode:
[0317] S1, preparing a first negative electrode slurry;
[0318] S1.1, mixing silicon powder and indium powder to form a first mixture;
[0319] S1.2, mixing the first mixed material, the binder PVDF, and the solvent NMP to form a first negative electrode slurry;
[0320] The mass ratio of indium powder, silicon powder and binder PVDF is 20:78.5:1.5; the particle size ratio of silicon powder to indium powder is 20:1;
[0321] S2, coating the first negative electrode slurry on at least one side of the negative electrode current collector, and forming a first negative electrode active material layer after drying;
[0322] S3, preparing a second negative electrode slurry;
[0323] S3.1, mixing silicon powder and indium powder to form a second mixture;
[0324] S3.2, mixing the second mixed material, the binder PVDF, and the solvent NMP to form a second negative electrode slurry; the mass ratio of indium powder, silicon powder, and binder PVDF is 20:78.5:1.5; the particle size ratio of silicon powder to indium powder is 20:1;
[0325] S4, coating the second negative electrode slurry on the first negative electrode active material layer to form a second negative electrode active material layer;
[0326] S5, after drying, a composite negative electrode is formed.
[0327] The thickness of the first negative electrode active material layer is 20 μm, and the thickness of the second negative electrode active material layer is 8 μm.
[0328] 3. Preparation of solid electrolyte membrane
[0329] The sulfide electrolyte Li6PS5Cl and the binder (PVDF) were mixed in a mass ratio of 99:1 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.
[0330] 4. Preparation of all-solid-state batteries
[0331] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.
[0332] Comparative Example 2
[0333] 1. Preparation of positive electrode:
[0334] NCM811, PTFE, super-P, and Li2ZrCl6 were mixed evenly in a mass ratio of 70:3:2:25, placed in a high shear force equipment mixer, subjected to fiberization treatment, formed a mixed material, and rolled the mixed material to form the first positive electrode layer; the rolling temperature was 60°C, and the rolling time was 5 minutes; the positive electrode current collector and the first positive electrode layer were stacked, hot pressed, and cooled to form a composite positive electrode. The hot pressing temperature was 150°C, the hot pressing time was 10 minutes, and the hot pressing pressure was 120Mpa;
[0335] 2. Preparation of negative electrode:
[0336] Silicon powder, binder PVDF, and solvent NMP are uniformly mixed to form a negative electrode slurry, and the negative electrode slurry is coated on a copper foil and dried to form a negative electrode.
[0337] The mass ratio of silica powder to binder PVDF is 99:1;
[0338] 3. Preparation of solid electrolyte membrane
[0339] The sulfide electrolyte Li6PS5Cl and polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 96:4 to obtain a mixture, which was ground for 30 minutes to obtain a sulfide electrolyte sheet. The obtained sulfide electrolyte sheet was hot rolled at a rolling temperature of 120° C. and a rolling time of 10 minutes.
[0340] 4. Preparation of all-solid-state batteries
[0341] The positive electrode prepared in step one, the negative electrode prepared in step two and the solid electrolyte membrane prepared in step three are assembled to form a battery.
[0342] Comparative experiment
[0343] A total of 13 groups of samples from the above-mentioned Examples 1-11 and Comparative Examples 1-2 were taken and the following tests were performed respectively. All test data were averaged and some values were rounded off.
[0344] 1. First discharge capacity test
[0345] At room temperature, the prepared battery was discharged at a constant current of 0.1C to a cut-off voltage of 3.0V to obtain the first cycle discharge capacity.
[0346] 2. Battery expansion test
[0347] The thickness of the prepared battery is d1, the thickness of the battery after 500 test cycles is d2, and the battery expansion rate = (d2-d1 / d1) 100%.
[0348] 3. 3C / 0.1C capacity retention rate
[0349] At room temperature, the prepared battery was discharged at a constant current of 0.1C to a cut-off voltage of 3.0V to obtain the first cycle discharge capacity.
[0350] 5. 500-cycle cycle retention rate
[0351] At room temperature, charge with a current of 0.1C to a charging cut-off voltage of 4.2V, switch to constant voltage charging to a cut-off current of 0.05C, let stand for 0.5h, then discharge with a current of 0.1C to a cut-off voltage of 3.0V, let stand for 0.5h, enter the next charge and discharge cycle, and so on, for a total of 500 charge and discharge cycles.
[0352] The test results are shown in the following table:
[0353]
[0354]
[0355] It can be seen from Examples 1-11 and Comparative Examples 1-2 in the above table that setting the active material layer into a double-layer structure and the mass proportion w2 of the second metal powder in the second negative electrode active material layer is greater than or equal to the mass proportion w1 of the first metal powder in the first negative electrode active material layer can effectively alleviate the expansion, powder shedding and other problems of silicon-based negative electrode materials and improve the capacity and cycle performance of the battery.
[0356] It should be pointed out that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite negative electrode for an all-solid-state battery, characterized in that: The composite negative electrode comprises a negative electrode current collector, a first negative electrode active material layer and a second negative electrode active material layer; The first negative electrode active material layer includes silicon powder and first metal powder; The second negative electrode active material layer includes silicon powder and second metal powder; The first negative electrode active material layer is disposed on at least one side of the negative electrode current collector, and the second negative electrode active material layer is disposed on a side of the first negative electrode active material layer away from the negative electrode current collector; A mass proportion w2 of the second metal powder in the second negative electrode active material layer is greater than or equal to a mass proportion w1 of the first metal powder in the first negative electrode active material layer.
2. The composite negative electrode according to claim 1, characterized in that The first metal powder and the second metal powder are independently selected from at least one of indium powder, tin powder, magnesium powder, copper powder, aluminum powder, and iron powder.
3. The composite negative electrode according to claim 2, characterized in that: The first metal powder is indium powder and / or the second metal powder is indium powder.
4. The composite negative electrode according to claim 1, characterized in that: The mass proportion w2 of the second metal powder in the second negative electrode active material layer is 50% to 80%; Preferably, the silicon powder accounts for 20% to 50% by mass in the second negative electrode active material layer.
5. The composite negative electrode according to claim 1, characterized in that: The mass proportion w1 of the first metal powder in the first negative electrode active material layer is 5% to 30%; Preferably, the silicon powder accounts for 70% to 95% by mass in the first negative electrode active material layer.
6. The composite negative electrode according to claim 1, characterized in that: The porosity of the first negative electrode active material layer is 4% to 8%; The porosity of the second negative electrode active material layer is 8% to 15%.
7. The composite negative electrode according to claim 1, characterized in that: The first negative electrode active material layer further includes a first binder; and / or, The second negative electrode active material layer further includes a second binder.
8. The composite negative electrode according to claim 1, characterized in that: The thickness of the second negative electrode active material layer is smaller than the thickness of the first negative electrode active material layer; The thickness of the first negative electrode active material layer is 10 μm to 30 μm; The second negative electrode active material layer has a thickness of 5 μm to 10 μm.
9. A method for preparing a composite negative electrode, characterized in that: The steps include: S1, mixing silicon powder, a first metal powder and a first binder in a solvent to prepare a first negative electrode slurry; S2, coating the first negative electrode slurry on at least one side of the negative electrode current collector, and forming a first negative electrode active material layer after drying; S3, mixing silicon powder, a second metal powder and a second binder in a solvent to prepare a second negative electrode slurry; S4, coating the second negative electrode slurry on the first negative electrode active material layer to form a second negative electrode active material layer; S5, after drying, a composite negative electrode is formed.
10. An all-solid-state battery, comprising a positive electrode, a solid electrolyte membrane and a composite negative electrode as described in any one of claims 1 to 8 or a composite negative electrode prepared by the method according to claim 9, wherein the composite negative electrode does not contain a solid electrolyte material and a conductive agent.
Citation Information
Cited By
Negative pole piece, preparation method thereof and solid-state battery
CN121035131A